2021
DOI: 10.1111/tan.14387
|View full text |Cite
|
Sign up to set email alerts
|

HLA genetic polymorphism in patients with Coronavirus Disease 2019 in Midwestern United States

Abstract: The experience of individuals with Coronavirus Disease 2019 (COVID-19) ranges from asymptomatic to life threatening multi-organ dysfunction. Specific HLA alleles may affect the predisposition to severe COVID-19 because of their role in presenting viral peptides to launch the adaptive immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this population-based case-control study in the midwestern United States, we performed high-resolution HLA typing of 234 cases hospitalized for CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…The rest 10 studies chose their study population from several countries around the world. Although different ethnicities were included in these studies, the association of HLA polymorphism, COVID‐19 and ethnicity were not exclusively explored, except in two studies, where they showed whites with DPA1*02:02 , 23 Hispanic people with DRB1*08:02 and younger African Americans with A*30:02 24 alleles were significantly more prone to COVID‐19 infection. All together both Class I and Class II HLA alleles were covered.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The rest 10 studies chose their study population from several countries around the world. Although different ethnicities were included in these studies, the association of HLA polymorphism, COVID‐19 and ethnicity were not exclusively explored, except in two studies, where they showed whites with DPA1*02:02 , 23 Hispanic people with DRB1*08:02 and younger African Americans with A*30:02 24 alleles were significantly more prone to COVID‐19 infection. All together both Class I and Class II HLA alleles were covered.…”
Section: Resultsmentioning
confidence: 99%
“…Six types of approaches were observed when it came to data sourcing for analysis, including both dry lab and wet lab, which are briefly discussed here—(i) HLA typing for both patient and control group were carried out in wet lab, frequency of different alleles were compared between two groups for any significant differences with different outcomes ( n = 9) 2,14,17,18,25,27,29,31,42 ; (ii) the most frequent HLA alleles were retrieved from AFND for the concerned countries of respected studies, SARS‐CoV‐2 genome was downloaded from NCBI or national databases and peptide binding capacity of frequent alleles was then evaluated using different version of NetMHCpan web server, association of strongly or weakly bound peptides with COVID cases and deaths per million (from worldometer, WHO situation report) were analyzed further through frequency analysis of HLA alleles, as it is established that strongly bound peptide are better presented and weakly bound peptides are poorly presented by MHC to T‐cells and thus can play a major role in adequate immune responses against COVID ( n = 6) 12,13,19–22 ; (iii) HLA allele frequency data for both patient and control group were obtained from national organ donor registry and COVID data from worldometer or national COVID registry, compared allele frequency between healthy and COVID group for identifying any association with COVID susceptibility or among mild, moderate or severe groups of COVID patients to associate HLA with COVID severity and/or mortality ( n = 9) 6,11,28,33,36,38,41,43,44 ; (iv) HLA typing in wet lab was opted for the patient group but reference group were selected from the population with known HLA type through donor registry and after that association with COVID susceptibility, severity or mortality were analyzed ( n = 6) 5,24,26,32,34,45 ; (v) in this approach, metagenomics data from patients were used to predict HLA type using HLA prediction software (HLAminer, OptiType, Seq2HLA, etc.) with or without control group ( n = 4) 1,23,35,40 ; (vi) lastly, two studies observed human monocyte HLA‐DR (mHLA‐DR) expression among healthy people and different clinical stages of COVID patients to identify any impact of altered mHLA‐DR expression with COVID‐19 prognosis ( n = 2) 37,39 (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations